1976
DOI: 10.1111/j.1748-1716.1976.tb10230.x
|View full text |Cite
|
Sign up to set email alerts
|

Isometric and Isotonic Length‐Tension Relations and Variations in Cell Length in Longitudinal Smooth Muscle from Rabbit Urinary Bladder

Abstract: Isometric and isotonic length-tension relations of longitudinal smooth muscle from rabbit urinary bladder were studied together with muscle cell length and tissue structure as revealed histologically. In vivo strip length at a bladder volume of 10 m1 is referred to as L10. The smooth muscle was relaxed by Ca2+-free solution and contracted by K+-high solution with different Ca2+-concentrations. Maximal active force, 12.5+/-0.4 N/cm2 (S.E., n =11), for wholestrips was attained at a length of 206+/-4% (S.E., n=5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
84
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 18 publications
10
84
1
Order By: Relevance
“…Although there is always a danger in extrapolating interpretation on one smooth muscle type to another, it could, however, be speculated that the very long functional length range (up to 10-fold change in length) of rabbit urinary bladder muscle (18) and pedal retractor muscle of Mytilus edulis (blue mussel) (8) could be due to a similar plastic mechanism described above.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is always a danger in extrapolating interpretation on one smooth muscle type to another, it could, however, be speculated that the very long functional length range (up to 10-fold change in length) of rabbit urinary bladder muscle (18) and pedal retractor muscle of Mytilus edulis (blue mussel) (8) could be due to a similar plastic mechanism described above.…”
Section: Discussionmentioning
confidence: 99%
“…In a muscle that displays length adaptation of active tension, one might expect that the passive length-tension curve will also length adapt (i.e., shift along the length axis). This seems especially relevant in the urinary bladder, a hollow organ that can accommodate large volumes at low luminal pressures during filling by lengthening DSM cells over sevenfold (52), which is over twofold greater than in striated muscles (14).…”
mentioning
confidence: 99%
“…The ability of airway smooth muscle (Pratusevich et al, 1995;Gunst et al, 1995) and probably other smooth muscles (Uvelius, 1976;Gillis et al, 1988) to adapt to changes in length and maintain maximal force generation over a large length range appears to require plastic changes in subcellular structures that involves rearrangement of contractile units within the contractile apparatus and reshaping of the apparatus itself. Rearrangement of the contractile units due to length adaptation is modeled in the present study to account for the observed length-dependent changes in ultrastructure and mechanical properties.…”
mentioning
confidence: 99%